Development of Innovation Strategies in the Technology Industry - Hidayat, Ade Rifki; Hermanto, Muhammad Yogi; Maulana, Muhammad Aldi; Sanjaya, Vicky F (Journal of Economics and Management, 2025)
The technology industry continues to grow rapidly, requiring companies to adopt innovation strategies to maintain competitiveness. This study aims to develop adaptive and sustainable innovation strategies to address the challenges and opportunities in the digital transformation era. The methodology used involves literature analysis, expert interviews, and case studies from leading technology companies. The results show that effective innovation strategies involve a combination of human resource management, investment in research and development, and the adoption of cutting-edge technologies. In addition, this strategy requires strong management support, cross-functional collaboration, and data-driven decision-making. The implications of these findings highlight the importance of fostering an innovation culture across the organization to create sustainable competitive advantage.